2014
DOI: 10.1002/cctc.201400009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Superhydrophobic Polymer Nanosphere Cage as a Framework for Miceller Catalysis in Biphasic Media

Abstract: This study demonstrated the use of a magnetic superhydrophobic polymer nanosphere cage derived from a Pickering emulsion as a framework for miceller catalysis in biphasic media. We designed this system through the covalent stabilisation of active site (2,2,6,6‐tetramethylpiperidine 1‐oxyl)‐grafted amphiphiles onto the magnetic hydrophobic core to form a micelle‐like architecture and used it as a Pickering emulsifier to develop a new kind of micelle‐catalysed biphasic system. The catalysis results reveal that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 81 publications
(15 reference statements)
0
16
0
1
Order By: Relevance
“…Finally, in addition to POM systems, Zheng et al reported very recently magnetic amphiphilic polystyrene nanospheres with covalently tethered 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO). [75] These catalysts showed a much higher activity than their soluble counterparts for the Montanari oxidation of a series of aromatic and aliphatic alcohols in w/o Pickering emulsions using NaClO as an oxidant (by a factor of 3). Furthermore, the catalysts could be efficiently recycled by magnetic decantation and reused for at least 10 times without significant loss of activity or degradation of magnetic susceptibility.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in addition to POM systems, Zheng et al reported very recently magnetic amphiphilic polystyrene nanospheres with covalently tethered 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO). [75] These catalysts showed a much higher activity than their soluble counterparts for the Montanari oxidation of a series of aromatic and aliphatic alcohols in w/o Pickering emulsions using NaClO as an oxidant (by a factor of 3). Furthermore, the catalysts could be efficiently recycled by magnetic decantation and reused for at least 10 times without significant loss of activity or degradation of magnetic susceptibility.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Finally, in addition to POM systems, Zheng et al. reported very recently magnetic amphiphilic polystyrene nanospheres with covalently tethered 2,2,6,6‐tetramethylpiperidine‐1‐oxyl (TEMPO) 75. These catalysts showed a much higher activity than their soluble counterparts for the Montanari oxidation of a series of aromatic and aliphatic alcohols in w/o Pickering emulsions using NaClO as an oxidant (by a factor of 3).…”
Section: Catalysis In Pickering Emulsions Stabilized By Catalytic mentioning
confidence: 99%
“…Außer den POM‐Systemen beschrieben Zheng et al. in einer neuen Arbeit magnetische amphiphile Polystyrolnanokugeln, an die 2,2,6,6‐Tetramethylpiperidin‐1‐oxyl (TEMPO) kovalent gebunden war 75. Diese Katalysatoren zeigten in der Montanari‐Oxidation von mehreren aromatischen und aliphatischen Alkoholen in Pickering‐Emulsionen mit NaClO als Oxidationsmittel eine weit höhere Aktivität (Faktor 3) als ihre löslichen Pendants.…”
Section: Katalyse In Durch Amphiphile Katalytische Nanopartikel Stunclassified
“…The catalysis results revealed that these fixed micelle-tethered TEMPO catalysts demonstrated a much higher activity than their soluble counterparts in the biphasic Montanari oxidation of alcohols, which could be due to the unique properties of Pickering emulsions and micellar catalysts. [14] However, the reason why catalyst-grafted nanoparticles can increase the reaction rate of the biphasic reaction system and how it enhances the reaction are still not clear. Little research has been performed to reveal the increase in activity of heterogeneous reactions contributed solely by the function of Pickering emulsion and how the surface properties contribute to the formation of such kind of emulsion.…”
Section: Introductionmentioning
confidence: 99%